Effectiveness of a Community-Based, Peer-Led, Literacy-Sensitive Diabetes Self-Management Education Program among Low-Literacy Adults with Type 2 Diabetes: A Non-Randomized Mixed-Methods Field Trial - Rajamanickam, Saranya; Rajendran, Vijaykumar; Surekha A; Suguna A; Britto, Rock (National Journal of Community Medicine, 2026)
Background: Peer-led and literacy-sensitive diabetes self-management education (DSME) has shown promise in improving outcomes among underserved populations with low literacy. The objective was to assess the observed effectiveness of a peer-led, literacy-sensitive DSME program on glycemic control and self-management behaviors among low-literate adults with type 2 diabetes. Methods: An explanatory sequential mixed-methods design was employed. In the quantitative phase, 160 adults with type 2 diabetes participated in a non-randomized controlled field trial conducted in community settings, with service-based allocation to intervention (n = 80) and usual care (n = 80). HbA1c was the primary outcome. Self-care behaviors, diabetes knowledge, and body mass index were secondary outcomes assessed at baseline and six months. Analysis of covariance and multivariable linear regression were applied. Results: At six months, the intervention group showed a greater reduction in HbA1c compared with usual care (adjusted mean difference -0.60%, 95% CI -0.95 to -0.25). Improvements in self-care behaviors and diabetes knowledge were also observed. Qualitative findings indicated that spoken and visual learning, teach-back, shared experiences, and peer accountability supported behavior change. Conclusion: The findings suggest that peer-led, literacy-sensitive DSME is associated with improved diabetes-related outcomes among low-literate adults when implemented under real-world community conditions.